Pengaruh Pendidikan Kesehatan Metode Simulasi Terhadap Keterampilan Pertolongan Pertama Luka Terbuka Pada Masyarakat - Sali Marla Papeti (FKIP, Universitas Palangka Raya, 2022)
An open wound or vulnus laceratum is one of the events that occurs due to sharp object injuries and blunt object collisions. Almost all the people around do not know how to do first aid for this type of wound. One of the steps that can be taken to increase knowledge of open wound first aid is to provide health educational simulation method.to find out the effect of health education simulation methods on open wound first aid skills in lay public society at village. The researchmethod use the Quasy Experiment, with a one group pre-post test method . The samples in this study taken 15 respondents by the accidental sampling techniques. The research instruments used is an observation sheet. Then the data collected processed by Mc Nemar Test. Findings , the Mc Nemarl test results obtained a p value = 0.001 with a significance of< 0.05. The conclusion is giving heakth education simulation methods on open wound first aid skills in lay public society at Tateli Village. The results of this study are expected to provide skill and knowledge to the society about open wound first aid.